Redox dysregulation and bioaccumulation of copper in tilapia Oreocromis niloticus - Carvalho, Solange de [UNESP]; Tavarez Ranzani Paiva, Maria Jose; Franca, Jakeline Galvao de [UNESP]; Neto, Francisco Filipak; Oliveira Ribeiro, Ciro Alberto de; Lombardi, Julio Vicente (Wiley-Blackwell, 2014)
The objective of this study was to evaluate the effect of two concentrations of copper (0.13 and 0.5mgL(-1)) on juveniles of tilapia, Oreocromis niloticus (Linnaeus), using two toxicological assays (I- copper exposure and II- copper exposure followed by recovery). Doses were taken from the liver of the test organisms to determine the concentrations of copper, reduced glutathione, activities of glutathione S-transferase and catalase, and lipid peroxidation. Exposure to copper in both assays resulted in significant accumulation of this metal in the analysed tissue and in decreased concentration of reduced glutathione. There was no alteration in the activities of catalase and glutathione S-transferase and in lipid peroxidation.
Keywords: Oreocromis niloticus (Linnaeus); oxidative stress; copper sulphate; tilapia; bioaccumulation